2021
DOI: 10.1039/d1gc01842f
|View full text |Cite
|
Sign up to set email alerts
|

Improved understanding of technical lignin functionalization through comprehensive structural characterization of fractionated pine kraft lignins modified by the Mannich reaction

Abstract: Amino alkylation of technical lignins via the Mannich reaction can be used as an analytical derivatization technique, but also in an applied manner to improve kraft lignin hydrophilicity or metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…148 It was also found that in the amination of lignin, its molecular weight had an effect on the degree of amination. 173 Lignins with a high molecular weight and low molecular weight were obtained through the solvent precipitation fractionation of pine kraft lignin. It was found that the lignin with a low molecular weight showed higher amine substitution regardless of the amine reagents and pH.…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…148 It was also found that in the amination of lignin, its molecular weight had an effect on the degree of amination. 173 Lignins with a high molecular weight and low molecular weight were obtained through the solvent precipitation fractionation of pine kraft lignin. It was found that the lignin with a low molecular weight showed higher amine substitution regardless of the amine reagents and pH.…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%
“…Moreover, amine substitution of pine kraft lignin took place selectively in the ortho position of the non-etherified phenolic hydroxyl groups. 173…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%
“…Therefore, these products have broad application prospects in many fields. 59 Similarly, Jiao et al used phenol to phenolize lignin and improve its chemical reactivity, increasing the number of active sites from 2.91 to 8.26 mmol/g. Then, the lignin was aminated using the Mannich reaction principle.…”
Section: Research Status Of Amphoteric Lignin Polymersmentioning
confidence: 99%
“…Formaldehyde was used as the second reagent to attach the amine functional group compounds to the ortho or para positions of the phenolic hydroxyl group in the lignin structure . In an alkaline or acidic medium, the high electron density lignin carbon will react with an intermediate (β-amino or carbonyl), which initially forms through the reaction of formaldehyde and amine. , Generally, lignin quaternary ammonium salt is insoluble at 4 < pH < 8 and dissolves under acidic (pH < 4) and alkaline (pH > 8) conditions. In addition, the introduction of cationic groups can also be accomplished using the substitution reaction on the lignin phenolic hydroxyl group …”
Section: Research Status Of Amphoteric Lignin Polymersmentioning
confidence: 99%
See 1 more Smart Citation